Washington, DC - Zimmerman, Karla; St Louis, Regis (Lonely Planet, 2015)
Climb the steps of the Lincoln Memorial, stare into Abe's stony eyes and read his Gettysburg Address chiseled in the wall. Stand where Martin Luther King, Jr. gave his famous speech and feel the sweep of history. Inside this book: full colour guide, free pull out city map, 87 bars, lounges and clubs, 35 pages of family friendly attractions, 24 free museums, 3 miles of lawn on the National Mall, 1 big White House comprehensive map, section DC for families, planning feature, range of planning tools, in depth coverage of top sights.